Dopaminergic correlates of metabolic network activity in Parkinson's disease. Issue 9 (3rd June 2015) - Holtbernd, Florian; Ma, Yilong; Peng, Shichun; Schwartz, Frank; Timmermann, Lars; Kracht, Lutz; Fink, Gereon R.; Tang, Chris C.; Eidelberg, David; Eggers, Carsten
Abstract Parkinson's disease (PD) is associated with distinct metabolic covariance patterns that relate to the motor and cognitive manifestations of the disorder. It is not known, however, how the expression of these patterns relates to measurements of nigrostriatal dopaminergic activity from the same individuals. To explore these associations, we studied 106 PD subjects who underwent cerebral PET with both 18F‐fluorodeoxyglucose (FDG) and 18F‐fluoro‐L‐dopa (FDOPA). Expression values for the PD motor‐ and cognition‐related metabolic patterns (PDRP and PDCP, respectively) were computed for each subject; these measures were correlated with FDOPA uptake on a voxel‐by‐voxel basis. To explore the relationship between dopaminergic function and local metabolic activity, caudate and putamen FDOPA PET signal was correlated voxel‐wise with FDG uptake over the entire brain. PDRP expression correlated with FDOPA uptake in caudate and putamen (P < 0.001), while PDCP expression correlated with uptake in the anterior striatum (P < 0.001). While statistically significant, the correlations were only of modest size, accounting for less than 20% of the overall variation in these measures. After controlling for PDCP expression, PDRP correlations were significant only in the posterior putamen. Of note, voxel‐wise correlations between caudate/putamen FDOPA uptake and whole‐brain FDG uptake were significant almost exclusively in PDRP regions. Overall, the data indicate that PDRP and PDCP expression correlates significantly with PET indices of presynaptic dopaminergic functioning obtained in the same individuals. Even so, the modest size of these correlations suggests that in PD patients, individual differences in network activity cannot be explained solely by nigrostriatal dopamine loss. Hum Brain Mapp 36:3575–3585, 2015. © 2015 Wiley Periodicals, Inc.